Α-fetoprotein producing hepatoid gastric adenocarcinoma with neuroendocrine differentiation: A case report. Issue 37 (September 2018) - Li, Tao; Liu, Tongjun; Wang, Min; Zhang, Mingwei
Abstract: Rationale: Hepatoid gastric adenocarcinoma is a rare type of gastric cancer. The phenomenon of neuroendocrine differentiation (NED) in gastrointestinal tumor needs further research. Both hepatoid adenocarcinoma and neuroendocrine differentiation are the factors leading to a poor prognosis of gastric cancer. However, there is still no specific treatment. Patient Concerns: A 60-year-old man who had a pain and distention in his upper abdomen presented melena. Gastroscopy and pathology revealed a gastric cancer. Diagnoses: Postoperative pathology revealed a hepatoid gastric adenocarcinoma. Immunohistochemical analysis showed a-fetoprotein (AFP), hepatocyte, synaptophysin (Syn), and chromogranin A (CgA) positive, and Ki67 60% positive. A-fetoprotein producing hepatoid gastric adenocarcinoma with NED is diagnosed. Interventions: The patient was treated with an R2 radical gastrectomy, but refused chemotherapy. Outcomes: The AFP level was >2000 ng/mL (0–8.78) half a year after the surgery. There was no obvious abnormality from computed tomography (CT). The patient refused positron emission tomography computed tomography (PET-CT) and left the hospital. Lessons: Hepatoid adenocarcinoma and neuroendocrine differentiation are the factors leading to a poor prognosis of gastric cancer. It relapses easily. Long-term follow-up and regular examinations are necessary to detect relapses.